Formal Reduction Of The Design System In Internal Spaces - Qadir Ahmad Alja, Salah Aldiyn (Opción, 2019)
The objective study (the formal reduction of the design system in the interior spaces) is an important matter in the interior design, where the study lies in clarifying the conceptual framework with its integrated meaning and their im- pact on interior designs has become inevitable for the existing urban areas and that the benefit from the formal organizations and their abbreviations is aes- thetically reflected on the designs and commensurate with the culture and cus- toms Society to keep pace with progress and unveil the ideas you have that you need to know and to try to benefit from them. For this reason, the researcher found that the first chapter includes formulating the research problem and its goal, which is summarized by the following question: Is formal reduction a role for the design system in the interior spaces? The second chapter also defines the theoretical framework to include the study of formal organiza- tions and their development through reduction. As for the third chapter of research procedures, the analytical descriptive approach was relied upon. The research community included the selective intentional method, after which the research sample model was determined. And then preparing the form (and the axis of analysis) to discuss the formal reduction of the design system, and in light of the results, the researcher concluded that achieving the reduction of formalism through performance through non-structural determinants was achieved by relying on several reduction mechanisms in relationships of dif- ference, contrast, and consistency, which generated attraction and attention and achieved Bass attraction.